PEMBUATAN KATALIS HETEROGEN BASA DARI SERBUK KAYU AKASIA - Zamhari, Mustain; ., Yuniar; Sari, Dita Indah; Saputri, Nuraldyla Suciaty (KINETIKA, 2019)
The purpose of this study was to produce heterogeneous catalyst based on activated carbon as a buffer impregnated with base solution and determine the effect of the concentration of a base solution and impregnation time. The ingredients used include acacia wood sawdust, hydrochloric acid (HCl), sodium hydroxide (NaOH), pottasium hydroxide (KOH) and aquadest (H2O). The study begins with the making of activated carbon from acacia wood sawdust by carbonizing the furnace at 500â„ƒ for 4 hours then washing 0.1 M HCl. After that, 15 grams of activated carbon are impregnated in NaOH and KOH with a concentration of 1, 2, 3, 4 and 5 N for 18, 21 and 24 hours. After the implementation, the catalyst was analyzed by AAS, FTIR and SEM. The best condition that produced the catalyst with the highest content after impregnation, which was 80.92% for NaOH dan 85.63% for KOH, was obtained at a concentration of 5 N for 21 hours. The application of catalysts heterogeneus base in biodiesel was made with a reaction time of 120 minutes at 60â„ƒ and the use of 3% b/b of used cooking oil.